Gender Stereotypes and Expected Backlash for Female STEM Students in Germany and Japan - Froehlich, Laura; Tsukamoto, Saori; Morinaga, Yasuko; Sakata, Kiriko; Uchida, Yukiko; Keller, Melanie M.; Stürmer, Stefan; Martiny, Sarah E.; Trommsdorff, Gisela (Frontiers in Education, 2022)
Although Germany and Japan are top-ranking in STEM, women are underrepresented in the STEM fields of physics, engineering, and computer science in both countries. The current research investigated widespread gender-science stereotypes in STEM in the two countries (Studies 1 and 2) and negative consequences of expected backlash (i.e., imagining negative reactions and lower ascribed communion in scenarios) for women’s emotions and motivation in STEM due to role incongruity and lack-of-fit (Study 3). Studies 1 (N = 87) and 2 (N = 22,556) showed that explicit and implicit gender-science stereotypes are widespread and comparable in Germany and Japan. Study 3 (N = 628) showed that lower ascribed communion was related to less positive emotions, more negative emotions and anxiety emotions, and less study motivation for STEM students (from the fields of physics, engineering, and computer science) from Germany and Japan. Results point to more subtle expected backlash effects for women in STEM than hypothesized. Theoretical and practical implications for gender equality in STEM are discussed.